Effective thickness of the planar detector in measurements of electrons energy loss - Deiev, O.S.; Kiprich, S.K.; Vasilyev, G.P.; Yalovenko, V.I.; Ovchinnik, V.D.; Shulika, M.Y. (Вопросы атомной науки и техники, 2017)
An experimental method of determining the active region thickness of Si planar detector was used. The method based on the dependence the depletion layer thickness from voltage applied to the detector (U = 0...60 V ). The electron energy loss spectra emitted by ⁹⁰Sr -⁹⁰Y in silicon planar detector were measured. The relative values of most probable energy loss of electrons were de ned for different thickness of detector. The planar detector was considered as a parallel-plate capacitor. The static (capacity) and dynamic (the detection efficiency and the energy deposit) characteristics had a root dependence on voltage.